2022
DOI: 10.3389/fpubh.2022.920233
|View full text |Cite
|
Sign up to set email alerts
|

To stay or to move? Investigation on residents' migration intention under frequent secondary disasters in Wenchuan earthquake-stricken area

Abstract: The deterioration of the living environment caused by the earthquake is the main migration motivation of residents in the area of the secondary earthquake disaster, and their migration intention is one of the most important factors affecting residents' happiness. This paper uses 957 effective survey samples from 12 secondary geological disaster areas after the Wenchuan earthquake to research the migration intention of residents and its influencing factors. It can be found that 45.2% of residents are willing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This case is typical of nuclear disasters, where multiple sites continue to be maintained, including evacuation centres and places of origin. Nuclear disasters differ significantly from others, such as tsunamis and typhoons; they involve concerns about radioactive contamination, which leads evacuees to leave their original residence for a long period [27][28][29][30]. The evacuation order described here lasted longer than the evacuees' expectation.…”
Section: Discussionmentioning
confidence: 82%
“…This case is typical of nuclear disasters, where multiple sites continue to be maintained, including evacuation centres and places of origin. Nuclear disasters differ significantly from others, such as tsunamis and typhoons; they involve concerns about radioactive contamination, which leads evacuees to leave their original residence for a long period [27][28][29][30]. The evacuation order described here lasted longer than the evacuees' expectation.…”
Section: Discussionmentioning
confidence: 82%
“…We conducted robustness checks in two ways. First, we added additional control variables regarding natural disasters, as previous studies have shown that the incidence or potential threat of natural disasters in an area could lower migrants’ willingness to live there [ 35 , 50 , 51 ]. Therefore, in our basic OLS model, we added a dummy variable indicating whether there have been tremendous hazards in the past ten years at the destinations.…”
Section: Resultsmentioning
confidence: 99%
“…Fourthly, for the channels, the four main channels that existed in the previous literature were the economic channel, agricultural channel, and urbanization channel, and if there is no specific channel, it will be an aggregate of channels. (Huang et al 2022) examined 957 survey samples from 12 disaster zones after the Wenchuan earthquake to understand the individuals' migration intentions and the factors influencing them. The study found that 45.2% are willing to migrate, indicating an instinctive desire for compensation and avoiding damage; however, this propensity has yet to result in a real decision.…”
Section: Introductionmentioning
confidence: 99%